Ten Years of Government Budgeting Research – A Review of Recommendations for Future Budgeting Practices - Endang Tri Pratiwi; Mediaty; Grace T Pontoh; Sri Sundari; Aini Indrijawati (Research Synergy Foundation, 2025)
Government budgeting serves not only as a financial document but also as a political instrument that reflects the priorities and values of society. Various types of budgeting have become the focus of research, with several research gaps identified, including the conditions that trigger changes in budgeting strategies, the different types of budgeting chosen, and pathways for future research that reflect important emerging and unexplored areas related to theory, context, characteristics, and methodology. This article aims to identify common issues related to the role of key persons and the budgeting cycle, with the goal of minimising gaps in the future budgeting practice literature. The use of PRISMA-SPAR4 through the Watase UAKE application resulted in a comprehensive search and strict supervision in this article, reducing the initial 133 articles to 43 articles based on keywords. The search for article data through the keyword